Biological Consequences of Exposure to Mechanical Vibration - Mario Bernardo-Filho; Debra Bemben; Christina Stark; Redha Taiar (SAGE Publishing, 2018)
A special issue of the journal Dose-Response entitled "Biological Consequences of Exposure to Mechanical Vibration" is proposed. When there is the interaction of physical agents, such as mechanical vibration to a body, physiological stress can be generated leading to expected and unexpected consequences. The aim is to describe effects due to the stress generated by the energy delivered in biological systems by mechanical vibration produced by different sources through studies involving human beings and experimental models. The evaluation of effects in molecular, cellular, and systemic level will contribute to increase the medical and biological knowledge about the interaction of mechanical vibration, as well as the understanding of the stress and mechanisms of the biological responses of the mechanical vibrations. The main topics will be related to neurophysiological responses to mechanical vibration generated in different sources, clinical approaches of the mechanical vibration generated in oscillating/vibratory platform, undesirable effect of the mechanical vibration generated in oscillating/vibratory platform, mechanical vibration in occupational activities, biological effects of ultrasound and infrasound, and quantification and physical approaches of the mechanical vibration.